Navigating the Complexities of Stroke. - Caplan, Louis R. (Neurology now books., 2013)
Strokes afflict thousands of people every year. Yet, for every fatal case, many more victims survive, often going on to live long, productive lives. Of course, none of it is simple-not preventing a ""brain attack, "" nor survival, rehabilitation, or living with cerebrovascular disease. The key is education, for both the moment of crisis and the long term. Navigating the Complexities of Stroke provides a practical guide for the lay public and medical professionals. Dr. Louis R. Caplan, one of the world's leading experts, guides readers through the subject in a straightforward and accessible mann.